2013
DOI: 10.1039/c3ra40347e
|View full text |Cite
|
Sign up to set email alerts
|

One-pot preparation of isocyanides from amines and their multicomponent reactions: crucial role of dehydrating agent and base

Abstract: One-pot preparation of isocyanides from amines and their multicomponent reactions: crucial role of dehydrating agent and base3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The synthesis of six-membered nitrogen-containing heterocycles including, poly-substituted 2,3dihydropyridin-4(1H)-one 335, 1,2,3,4-tetrahydropyridine 336, and pyridine derivatives, was 219 . It was found that the entity of base and dehydrating agent and their amounts played important roles in this procedure.…”
Section: Pyridinementioning
confidence: 99%
“…The synthesis of six-membered nitrogen-containing heterocycles including, poly-substituted 2,3dihydropyridin-4(1H)-one 335, 1,2,3,4-tetrahydropyridine 336, and pyridine derivatives, was 219 . It was found that the entity of base and dehydrating agent and their amounts played important roles in this procedure.…”
Section: Pyridinementioning
confidence: 99%
“…Finally, our study was completed by taking advantage of the mildness of our catalytic conditions to develop a one‐pot procedure for the direct preparation of isocyanide 10 from benzylamine . Among the various possible reagents that are able to dehydrate a formamide, the Burgess reagent was foreseen as being the most compatible upon using DMF as the solvent.…”
Section: Figurementioning
confidence: 99%
“…NFormyl compounds have been used as precursor for the synthesis of formamidines [1], isocyanides [2], aminocarbonylation of aryl halides [3], and as reagents in the classical Vilsmeier formylation reactions [4]. Furthermore, they are valuable intermediates in the construction of various medicinally important compounds such as quinolone antibiotics [5] and cancer chemotherapeutic agents [6].…”
Section: Introductionmentioning
confidence: 99%